THE METAETHICAL IMPLICATIONS OF GOD'S ONTOLOGICAL STATUS IN TANTRIC TEACHINGS: A PHILOSOPHICAL STUDY OF CALON ARANG MANUSCRIPTS - Fattah, Galuh Nur; Dewantri, Puja Alviana; Tangrestu, Venessya; Laras, Valentin Gagah (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2024)
This study aims to investigate the ontological status of God in Calon Arang Manuscripts and interpret it metaethically. Calon Arang, as an original Tantric literary work from the Nusantara's ancestors, is an interesting subject to examine in terms of its ontological view of God and the ethical implications that arise from it. Tantrism essentially conceptualizes God dualistically, depicting God in conflicting forms or elements, which are considered the cosmic basis of the world. This study highlights such dualistic tendencies and identifies potentially significant metaethical implications. An in-depth analysis is conducted utilizing a metaethical approach, specifically the school of natural determinism. This school believes that the moral laws that apply in human reality are in accordance with natural laws, so humans cannot determine objective morality with certainty. The ethical implications of God's ontological status in Tantric teachings are understood as a result of this natural determinism. This research places God's ontological status as the material object and uses natural determinism as the formal framework. Research methods include description, holistics, deduction-induction, and heuristics. With this approach, this research seeks to detail and unravel the complexity of the ontological view of God in the Calon Arang Manuscripts, while exploring the ethical implications that can bring a deeper understanding of this Tantric text.